Sigmoid volvulus in pregnancy: a case report - Jay Lodhia (BMC, 2021)
Abstract Introduction Sigmoid volvulus in pregnancy is a rare cause of intestinal obstruction with high maternal and fetal morbidity and mortality if not diagnosed and managed early. Case presentation A 29-year-old female (Chagga by tribe) presented with clinical features of intestinal obstruction 24 weeks into her second pregnancy. She had symptoms for one week. An emergency laparotomy was performed whereby gangrenous sigmoid volvulus was found; thus, it was resected and Hartmann’s colostomy was raised. Unfortunately, she experienced intrauterine fetal death post-operatively. She was discharged clinically stable. Conclusion Early diagnosis and management can prevent adverse effects such as bowel ischemia and preterm labor. Because classic clinical and radiological features may not be evident, high degree of suspicion is warranted.